Analisis Sistem Tunjangan Kinerja Daerah (TKD) Dalam Meningkatkan Kinerja Individual Kantor Bupati Langkat - Marsheila, Naura; Hasibuan, Nur Fadhilah Ahmad (Maisyatuna, 2024)
This research discusses the performance allowance system (pay-for-performance), which is a more modern and progressive system and is expected to improve employee performance significantly. The aim is to analyze the Regional Performance Allowance (TKD) system in improving the individual performance of the Langkat Regent's office. The research method used is a descriptive qualitative approach, and the data analysis technique used is through interviews and documentation. The results of the research show that the Regional Performance Allowance (TKD) system in improving the individual performance of the Langkat Regent's office is quite good, this is shown in the performance sheet management system in providing performance allowances which uses the SIMPEG E-Kinerja application, thereby simplifying and speeding up the reporting process. However, there are still weaknesses, namely the existence of organizational behavior that cannot be overcome, for example crab mentality, allowances provided by agencies that are not in accordance with the performance of State Civil Apparatus (ASN) who are late in coming to the office, do not come to the office, employees who leave their duties during working hours without permission, delays in incentive payments at the Langkat Regent's Office. Therefore, some employees feel unfair in the performance allowances they receive, and this causes competition between employees, they become lazy and less motivated to work hard, until in the end they prefer to just work as it is.